Lifetime : the amazing numbers in animal lives - Schaefer, Lola M., 1950-; Neal, Christopher Silas (San Francisco : Chronicle Books, 2013)
Provides number-related facts about the lives of a variety of animals, such as the the number of antlers a caribou will grow and shed in a lifetime.
5.1
K-3
Keywords: Developmental biology -- Juvenile literature; Life expectancy -- Juvenile literature; Animals -- Pictorial works -- Juvenile literature; Biology; Life expectancy; Animals -- Pictorial works; Biology; Life expectancy; Animals -- Pictorial works; Picture books for children